2019
DOI: 10.1016/j.cma.2019.04.043
|View full text |Cite
|
Sign up to set email alerts
|

A multi-physics peridynamics-DEM-IB-CLBM framework for the prediction of erosive impact of solid particles in viscous fluids

Abstract: In this paper, a new fully-resolved framework capable of capturing the fundamental physics of particle-fluid interactions, the collision of particles with solid surfaces, and the resulting damage is proposed. A coupled DEM-IB-CLBM, consisting of a discrete element method (DEM), an immersed boundary (IB) method, and a cascaded lattice Boltzmann method (CLBM), is used to fully resolve the interaction of the particles with the surrounding viscous fluid. The peridynamics theory is then implemented and used to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 28 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…The accumulation of broken bonds leads to material damage. The damage of a material point is assessed with the ratio of the number of broken bonds to all the bonds of the material point, which equals one when a material point loses all its bonds [39].…”
Section: The Peridynamic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of broken bonds leads to material damage. The damage of a material point is assessed with the ratio of the number of broken bonds to all the bonds of the material point, which equals one when a material point loses all its bonds [39].…”
Section: The Peridynamic Theorymentioning
confidence: 99%
“…Coupling of the fluid and solid solvers using a partitioned approach can be achieved through a weak or strong scheme. We have previously developed a weak scheme to couple the peridynamic model with the IB-CLBM solver [39] by launching the two solvers sequentially. It has been demonstrated that this multi-physics computational framework can predict the erosive impact of solid particles in a flow correctly.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these advantages, it has been successfully applied to crack propagation problems [21,22], composite material damage [23,24], fluid mechanics and acoustics [25], and heat conduction analysis [26,27] etc. There are several kinds of peridynamics, such as bond-based PD [19], state-based PD [28], and element-based PD [29] etc., and they can be easily coupled with other numerical methods to deal with the interaction between different materials, such as PD-FEM [30], PD-SPH [31], and PD-DEM [32].…”
Section: Introductionmentioning
confidence: 99%
“…The same authors proposed later a coupled peridynamic thermo-mechanic model starting from thermodynamic considerations [18], and using explicit schemes to approximate the solutions of the peridynamic equations. Other applications of peridynamics for thermo-mechanics or other multi-physics problems can be found in [19,20]. In the context of electrical conduction and coupled electro-mechanical models, Prakash and Seidel [2] developed a classical bond-based formulation for the study of the piezoresistive response of carbon nanotube reinforced polymer nanocomposite materials.…”
Section: Introductionmentioning
confidence: 99%